THE ROLE OF ANTIBODIES IN GYNECOLOGICAL TUMORS - Maxarova Moxinur Baxtiyor qizi; Salohiddinova Rushana Kamoliddinxon kizi; Musayeva Zubayda Umar kizi; Sokhibova Shakhnoza (TADQIQOTLAR, 2025)
Annotation:  During  the  last  decades,  several  improvements  in  treating gynecological malignancies have been achieved. In particular, target therapies, mostly monoclonal antibodies, have emerged as an attractive option for the treatment of these malignancies. In fact, various molecular-targeted agents have been developed for a variety of malignancies with the objective to interfere with a precise tumor associated receptor, essential for cancer cell survival or proliferation, blocking its function, of the cancer cells. This article examines the role of antibodies in the diagnosis, treatment, and monitoring of gynecological tumors, including ovarian, cervical, and endometrial cancers. It highlights how monoclonal antibodies and antibody-based therapies, such as antibody-drug conjugates and immune checkpoint inhibitors, are being used to target tumor-specific antigens.